(untitled) (UNWE Yearbook, 2021)
This article examines the methodologies used by global and national organizations specialized in the study of media freedom, namely US-based Freedom House and International Research & Exchanges Board (IREX); French-based Reporters Without Borders (RSF); Italian-based Center for Media Pluralism and Media Freedom (CMPF), which is funded by the European Commission, and the Association of European Journalists – Bulgaria (AEJ-Bulgaria). Employing a critical approach and a comparative analysis, this study outlines the approaches and tools used to measure freedom of the media, the social, political and economic factors that influence the results, and the Bulgarian perspective in the indices of these organizations.